You can "complete the square" by adding 13 to both sides of the equation

x^2 + 6x + 9 = 13 (you need to recognize that you want to end with a constant of (6/2)^2 = 9 on the left side. Starting from -4, this means you add 13.)

(x+3)^2 = 13 (rewrite as a square. This is the form we were trying to get to.)

Now, take the square root and subtract 3

x+3 = ±√13

√13 ≈ 3.60555, so x is approximately -6.60555, +0.60555.

**.**x^2 + 6x - 4 = 0x^2 + 6x + 9 = 13 (you need to recognize that you want to end with a constant of (6/2)^2 = 9 on the left side. Starting from -4, this means you add 13.)

(x+3)^2 = 13 (rewrite as a square. This is the form we were trying to get to.)

Now, take the square root and subtract 3

x+3 = ±√13

**x = -3 ± √13**_____√13 ≈ 3.60555, so x is approximately -6.60555, +0.60555.